Spy walker: a convenient way to assess gait in walker assistive devices - Viegas, V. (2019)
This paper presents the Spy Walker, a measurement system intended to characterize gait in walker assistive devices. The proposed system can be easily integrated into any commercial walker without any loss of native functionality. The system makes use of e-textile electrodes to sense the heart rate of the user, load cells to measure the force applied on the walker legs, and an inertial measurement unit to sense motion and orientation. These signals are sampled locally and then transferred over a Bluetooth link to a remote host where they are processed in real time. Data processing includes the detection, classification and characterization of steps. A rich set of parameters is presented for each step, including estimates of unbalance and motor incoordination, travelled distance and azimuth, and lift of the walker frame. This information can be used by a physiotherapist to assess objectively the physical condition of the user, and tune the rehabilitation therapy if needed.